Cyberbullying in Society: An Analysis from the Perspectives of Victims, Perpetrators, and Authorities - Yasin, Redwan; Wan Haniff, Wan Amir Azlan; Ali, Alizah; Atan, Siti Mariam; Mohd Salleh, Rosnani; Ismail, Noraini (Advances in Social Sciences Research Journal, 2025)
Cyberbullying remains a widespread issue with serious psychological and legal consequences. This study explores the social and digital dimensions of cyberbullying in Malaysia by examining perceptions from three perspectives: victim, perpetrator, and authority. Guided by the Third-Person Effect Theory, a 15-item questionnaire was administered to 193 undergraduate students at Universiti Teknologi MARA, Segamat, Johor. Each item was rated on a 5-point Likert scale. Findings reveal that respondents believe others are more emotionally affected by cyberbullying, more vulnerable to reputational harm, and more likely to experience anxiety and depression than themselves. They also perceive others as more likely to post harmful content and justify offensive online behavior. From the authority perspective, participants feel others are less informed about digital safety, more dependent on law enforcement, and less aware of legal remedies. These self–other perceptual gaps reflect the third-person effect and highlight the need for targeted interventions. Based on the findings, it is recommended that anti-cyberbullying strategies move beyond general awareness to include interactive, reflective, and community-driven initiatives that address the self–other bias and foster personal accountability. Integrating the Third-Person Effect as a core framework in digital literacy programs and policy design can enhance self-awareness and collective responsibility in preventing and responding to cyberbullying.